Get it on Google Play
Q.4 Find the value of:
(i) -4 ÷ \(\frac{2}{3} \)
(ii) \(\frac{-3}{5} \) ÷ 2
(iii) \(\frac{-4}{5} \) ÷ (-3)
(iv) \(\frac{-1}{8} \) ÷ \(\frac{3}{4} \)
(v) \(\frac{-2}{13} \) ÷ \(\frac{1}{7} \)
(vi) \(\frac{-7}{12} \) ÷ \((\frac{-2}{13}) \)
(vii) \(\frac{3}{13} \) ÷ \((\frac{-4}{65}) \)
Answer :

(i) -4 ÷ \(\frac{2}{3} \)= -4 × \(\frac{3}{2} \) = \(\frac{-12}{2} \)= -6
(ii) \(\frac{-3}{5} \) ÷ 2 = \(\frac{-3}{5} \) ×\(\frac{1}{2} \)= \(\frac{-3}{10} \)
(iii) \(\frac{-4}{5} \) ÷ (-3) = \(\frac{-4}{5} \)× \(\frac{-1}{3} \) =\(\frac{4}{15} \)
(iv) \(\frac{-1}{8} \) ÷ \(\frac{3}{4} \) = \(\frac{-1}{8} \) × \(\frac{4}{3} \) = \(\frac{-4}{24} \) = \(\frac{-1}{6} \)
(v) \(\frac{-2}{13} \) ÷ \(\frac{1}{7} \) = \(\frac{-2}{13} \)×7 = \(\frac{-14}{13} \)=\(-1\frac{1}{13} \)
(vi) \(\frac{-7}{12} \) ÷ \((\frac{-2}{13}) \)= \(\frac{-7}{12} \) × \((\frac{13}{-2}) \)=\(\frac{-91}{-24} \) = \(3\frac{19}{24} \)
(vii) \(\frac{3}{13} \) ÷ \((\frac{-4}{65}) \) = \(\frac{3}{13} \) × \((\frac{65}{-4}) \) = \(\frac{195}{-52} \)
= \(\frac{195÷13}{-52÷13} \)=\(\frac{15}{-4} \)=\(-3\frac{3}{4} \)